Trends in survival, neonatal morbidity and neurodevelopmental outcome of very preterm infants in Tainan, Southern Taiwan, 1995–2016 - Lan-Wan Wang; Yung-Chieh Lin; Shan-Tair Wang; Chao-Ching Huang; Kuo-Inn Tsou; Po-Nien Tsao; Shu-Chi Mu; Chyong-Hsin Hsu; Reyin Lien; Hung-Chih Lin; Chien-Chou Hsiao; Chao-Ching Huang; et al. (Journal of the Formosan Medical Association, 2021)
Background: Using regression modeling analysis to investigate the breakpoints of the trends in survival-without-major-neonatal-morbidities (MNM) or -without-neurodevelopmental- impairment (NDI) by year and gestational age (GA) in preterm infants. Methods: We enrolled 2237 preterm infants (GA < 32 weeks) in Tainan, Taiwan. The trends in survival-without-MNM or -without-NDI by year (1995–2016) and GA (23–31 weeks), and the epochs and GA ranges with distinct changes were examined. Adjusted rate ratios (aRR) (95% confidence interval [CI]) were calculated using the rates in infants born at 23 weeks in 1995 as the reference. Results: For yearly trend, there were three epochs (1995–2000, 2001–2006, 2007–2016) with distinct changes in the rates of survival-without-MNM (aRR [95% CI] 1.07 [1.02–1.12], 1.04 [1.02–1.07], 1.02 [1.01–1.04]) and -without-NDI (1.03 [1.02–1.07], 1.02 [1.01–1.04], 1.01 [0.98–1.04]). For GA trend, the three GA ranges with different increases in the rates of survival-without-MNM were 23+0-26+6 (1.60 [1.31–1.94]), 27+0-28+6 (1.24 [1.14–1.34]) and 29+0-31+6 weeks (1.17 [1.02–1.34]), while those in the rates of survival-without-NDI were 23+0-25+6 (1.14 [1.03–1.25]), 26+0-28+6 (1.06 [1.02–1.12]) and 29+0-31+6 weeks (1.04 [1.02–1.07]). The trends in survival-without-MNM and -without-NDI increased over years in infants with GA 25–31 but not < 25 weeks. Conclusion: The yearly trends in survival-without-MNM and -without-NDI had steady increases from 1995 to 2016 with distinct changes in three epochs, and the GA trends also increased with different rates per week in three GA ranges. Infants with GA < 25 weeks did not improve on the rates of survival-without-MNM or -without-NDI per year from 1995 to 2016.